Pengaruh Alokasi Dana Desa dan Dana Desa Terhadap Kesejahteraan Masyarakat Desa - Sefnat Aristarkus Tang; Yustina Maro; Alvonso Fanisius Gorang; Elia Maruli (Peneliti.net, 2022)
Community welfare is an inseparable part of the paradigm of economic development that is said to be successful if the level of community welfare is getting better. Gaps and inequality in people's lives are caused by the success of economic development that is not accompanied by an increase in people's welfare. The purpose of the study was to determine the effect of village fund allocation on the welfare of the village community in Bana Village, Pantar District, Alor Regency, to determine the effect of village funds on the welfare of the village community in Bana Village, Pantar District, Alor Regency and to determine the effect of allocation of village funds and village funds on community welfare. Village in Bana Village, Pantar District, Alor Regency. The sample in this study was 64 people. Data collection using observation techniques, questionnaires, and documentation studies. Then analyzed using a t-test (partial test) and F-test (simultaneous test). The method used in this research is descriptive statistics, research instrument test, and classical assumption test. The results showed that the variable allocation of village funds and village funds had a significant effect on the welfare of rural communities in Bana Village, Pantar District, and Alor Regency